Pingyin rose essential oil alleviates LPS-Induced inflammation in RAW 264.7 cells via the NF-κB pathway: an integrated in vitro and network pharmacology analysis - Rifat Nowshin Raka; Ding Zhiqian; Yuan Yue; Qiao Luchang; Park Suyeon; Xiao Junsong; Wu Hua (BMC, 2022)
Highlights ➢ PREO is a mixture of aromatic components, mainly monoterpenoids. ➢ PREO reduces the expression of proinflammatory cytokines and oxidative stress markers. ➢ Network pharmacological studies indicated that PREO might downregulate inflammation through the NF-κB  signaling pathway, and these results were confirmed by Western blot investigation. ➢ Molecular docking analysis revealed the potential of these compounds as possible ligands. Graphical Abstract